THE VERSION REGARDING SPECIAL SERVICES OF THE ISLAMIC REPUBLIC OF IRAN FOR INVOLVEMENT IN THE DEATH OF THE SSNG K-141 "KURSK" IN THE CONTEXT OF MARITIME SAFETY, SECURITY AND DEFENCE OF THE WOLD - KALINICHENKO, Oleksandr; SIMONENKO, Olena (Zenodo, 2024)
The geopolitical evolution of Iran in the 21st century was considered. Versions regarding the death of the "Kursk" APRK are listed. Attention is focused on the controversy of the Pacific submariners, who in one way or another are involved in the analyzed character: Valery Ryazantsev - my first chief officer of the SSN K-45 and Maksym Klimov - the commander of the mine-torpedo combat department of the third generation Pacific nuclear submarines of projects 971 and 949A. Attention was drawn to the aspects and motives of the interested parties regarding the transfer of cavitating torpedoes, as well as to the cross-species and international composition of the participants in the military exercises in the waters of the Barents Sea, the management of which clearly went beyond the powers of the Commander of the Northern Fleet of the Russian Navy. The facts on which the author of the version relied were given. Chronological, comparative, problem methods of historical scientific research and the method of content analysis are applied. Cause-and- effect relationships of certain events were revealed, which created a logical chain that led not only to the fact of the death of the SSNG K-141, but also to the subsequent appearance of high-speed cavitation underwater rocket-torpedoes in the armed forces of the Islamic Revolutionary Guard Corps naval forces. For this purpose, the military-geographical and military-historical realities of the Persian Gulf of the last quarter of the 20th and the first quarter of the 21st centuries were considered. Conclusions were made regarding the possibility and argumentation of the author's version regarding the motives, direct actions and involvement of Iranian specialists in the SSNG "Kursk" tragedy.